Intestinal transplantation: review of operative techniques - Nickkholgh, Arash; Contin, Pietro; Abu-Elmagd, Kareem; Golriz, Mohammad; Gotthardt, Daniel; Morath, Christian; Schemmer, Peter; Mehrabi, Arianeb (Clinical transplantation, 2013)
The improvement of outcomes in intestinal transplantation (ITx) over the last two decades has been made possible through standardization in surgical techniques, improvements in immunosuppressive and induction protocols, and post-operative patient care. From a surgical technical point of view, all different types of small bowel containing transplants can be categorized into three main prototypes, including isolated small bowel, liver-small bowel, and multivisceral transplantations. In this review, we describe these three main prototypes and discuss the most important technical modifications of each type, as well as donor and recipient procedures, and highlight the more recent operative technical topics of discussion in the literature.
Gesehen am 22.11.2021